Purification and Partial Characterization of Trypsin-Specific Proteinase Inhibitors from Pigeonpea Wild Relative Cajanus platycarpus L. (Fabaceae) Active against Gut Proteases of Lepidopteran Pest Helicoverpa armigera - Swathi, Marri; Mishra, Prashant K.; Lokya, Vadthya; Swaroop, Vanka; Mallikarjuna, Nalini; Dutta-Gupta, Aparna; Padmasree, Kollipara (Frontiers in Physiology, 2016)
Abstract Proteinase inhibitors (PIs) are natural defense proteins of plants found to be active against gut proteases of various insects. A pigeonpea wild relative Cajanus platycarpus was identified as a source of resistance against Helicoverpa armigera, a most devastating pest of several crops including pigeonpea. In the light of earlier studies, trypsin-specific PIs (CpPI 63) were purified from mature dry seeds of C. platycarpus (ICPW-63) and characterized their biochemical properties in contributing to H. armigera resistance. CpPI 63 possessed significant H. armigera gut trypsin-like proteinase inhibitor (HGPI) activity than trypsin inhibitor (TI) activity. Analysis of CpPI 63 using two-dimensional (2-D) electrophoresis and matrix assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry revealed that it contained several isoinhibitors and small oligomers with masses ranging between 6-58 kDa. The gelatin activity staining studies suggest that these isoinhibitors and oligomers possessed strong inhibitory activity against H. armigera gut trypsin-like proteases (HGPs). The N-terminal sequence of the isoinhibitors (pI 6.6 and pI 5.6) of CpPI 63 exhibited 80% homology with several Kunitz trypsin inhibitors (KTIs) as well as miraculin-like proteins (MLPs). Further, modification of lysine residue(s) lead to 80% loss in both TI and HGPI activities of CpPI 63. In contrast, the TI and HGPI activities of CpPI 63 were stable over a wide range of temperature and pH conditions. The reported results provide a biochemical basis for pod borer resistance in C. platycarpus.